(untitled) (Eurasian Medical Research Periodical, 2023)
Modern rheumatology pays special attention to the detection of diseases at the earliest possible stages. To date, there is evidence that the preclinical period of a systemic autoimmune reaction is associated with dysregulation of immune interactions with synanthropic microflora. The article deals with the issues of violation of the microbial landscape in rheumatological patients and the impact on the microbiont of the stomach and intestines of drugs used to treat rheumatological diseases